Impact of social responsibility on the image and reputation of entrepreneurships: a systematic literature review from 2021 to 2025 - Velezmoro López, José Antonio; Gómez Ramirez, Guian Franco; Angeles Roque, Luz Zarai (LACCEI, 2025)
Startups face a series of business challenges that require them to manage an effective and ethical image and reputation. This review aims to demonstrate the impact of corporate social responsibility on the image and reputation of startups. Thus, 30 scientific articles have been collected between the years 2021-2025, from Scopus, Dialnet, Alicia, Web of Science, Google Scholar and Scielo. For the selection, inclusion and exclusion criteria related to the title, keywords, publication date, whether it is freely accessible, and type of research have been taken into account. It was detected that in the years 2021 and 2023 there were more publications with 9 articles each. It is concluded that corporate social responsibility has a positive impact on the image and reputation of emerging companies, because stakeholders are more interested in purchasing products from socially responsible companies because they observe the actions towards the community in which they live. In addition, by applying these practices, an improvement in the image and perception of companies was observed. Finally, it also highlights that companies must have a social responsibility plan with sustainable practices to be implemented in different communities.